Energy-Efficient Approach for Beamforming Design and BBUs Aggregation in Heterogeneous C-RAN - Mostafa M. Abdelhakam; Mahmoud M. Elmesalawy (International Telecommunications Society (ITS), 2019)
Heterogeneous cloud radio access network (C-RAN) that combines the benefits of C-RAN and multi-tier heterogeneous networks (HetNets) is emerged as a novel network solution for improving both spectrum and energy efficiencies. In this work, we propose an energy-efficient approach that considers both RRHs beamforming design and BBUs aggregation in heterogeneous C-RAN. First, the problem is formulated as an optimization problem to maximize the weighted energy efficiency utility function subject to BBU processing capability, per-user quality-ofservice (QoS) requirement and per-RRH total transmit power constraints. Then, the optimization problem is decomposed into two sub problems. The first sub problem is a transmit beamforming vectors optimization problem. This problem is transformed to a weighted sum mean square error (MSE) minimization problem and solved using a weighted minimum mean square error (WMMSE) algorithm. The second sub problem is the BBUs aggregation problem. This problem is converted to a bin packing problem and we propose an algorithm based on the Best-Fit-Decreasing method to solve it. In order to show the effectiveness of the proposed energy-efficient approach, we compare it with different algorithms that are presented in the literature.
Keywords: 330; Heterogeneous cloud radio access network; beamforming; weighted minimum mean square error (WMMSE); BestFit-Decreasing